Dasatinib suppression of medulloblastoma survival and migration is markedly enhanced by combining treatment with the aurora kinase inhibitor AT9283 - Petersen, William (2014)
Medulloblastoma (MB) expresses Src kinase, while aurora kinase A overexpression correlates with poor survival. We thus investigated novel combination treatment with dasatinib and AT9283, inhibitors of Src and aurora kinase, respectively, on MB growth in vitro and in vivo. Treatment with each drug significantly reduced cell viability and combined treatment markedly potentiated this response. AT9283 induced p53 expression, autophagy, and G2/M cell-cycle arrest, while combined treatment induced S phase arrest. Dasatinib treatment caused tumor regression in vivo. Activated Src was detected in 44% MB analyzed. We conclude that further evaluation of this combination therapy for MB is highly warranted.